1984
DOI: 10.1007/bf00279314
|View full text |Cite
|
Sign up to set email alerts
|

Gene frequencies of S-adenosylhomocysteine hydrolase (SAHH) in a Japanese population

Abstract: Genetic polymorphism of S-adenosylhomocysteine hydrolase (SAHH) was investigated in a total of 214 red blood cell samples from unrelated Japanese using the starch gel electrophoresis and the enzyme-specific staining procedures. Three common phenotypes were observed which corresponded to SAHH 1, SAHH 2-1, and SAHH 2, controlled by two alleles, SAHH*1 and SAHH*2. The estimated gene frequencies of SAHH*1 and SAHH*2 in Japanese were 0.953 and 0.047, respectively. This result was not different from European samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
2

Year Published

1986
1986
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 4 publications
1
7
2
Order By: Relevance
“…Four different SAHH phenotypes could be recognized in the samples analysed and they are referred to as types SAHH 1, 2-1, 2 and 3-1. Three of them, 1, 2-1 and 2, appear identical to those described by Bissbort et al (1983) and Akiyama et al (1984). The fourth pattern, called SAHH 3-1, seems to coincide with that reported by Bissbort et al (1983) as a rare variant segregating in one family.…”
Section: Electrophoretic Properties Of Sahh Isozyrnessupporting
confidence: 69%
See 1 more Smart Citation
“…Four different SAHH phenotypes could be recognized in the samples analysed and they are referred to as types SAHH 1, 2-1, 2 and 3-1. Three of them, 1, 2-1 and 2, appear identical to those described by Bissbort et al (1983) and Akiyama et al (1984). The fourth pattern, called SAHH 3-1, seems to coincide with that reported by Bissbort et al (1983) as a rare variant segregating in one family.…”
Section: Electrophoretic Properties Of Sahh Isozyrnessupporting
confidence: 69%
“…A rather small number of families, however, has been studied from this viewpoint. As far as population studies are concerned, the data are so scanty (Bissbort et al 1983; Akiyama et al 1984; Corbo et al 1985) that, so far, little is known about the incidence of SAHH phenotypic variation in different ethnic groups.…”
Section: Introductionmentioning
confidence: 99%
“…of eq. (7) and can, in principle, be computed by inverting the coupling matrix (5). In practice, this involves a computationally expensive process and, thus, we adopt a different strategy based on a direct minimization of the Helfrich Hamiltonian.…”
Section: A Energy Calculationsmentioning
confidence: 99%
“…These adhesion bonds often aggregate into macroscopically large adhesion clusters, such as focal adhesions, adherens junctions and gap junction plaques [2][3][4]. In addition to providing mechanical stability to cells, these adhesion domains are essential for numerous biological processes, including signal transduction [5], T-cell activation [6], and tissue formation [7]. Therefore, it is paramount to gain a comprehensive understanding of the biophysical principles that govern the formation of adhesion clusters.…”
Section: Introductionmentioning
confidence: 99%
“…Mohandas et al [ 1984] showed that SAHH is located on the long arm of chromosome 20 in the region cen -q 13.1, proximally to adenosin deaminase (ADA; q 13.2 -qter). Very low levels of SAHH activity have been found in children af fected by deficiency of ADA (< 2% of nor mal SAHH activity) [Hershfield et al, 1979], purine nucleoside phosphorylase (PNP; about 15% of normal SAHH activ ity) and hypoxanthine-guanine phosphorybosyl transferase (HGPRT; about 43% of normal SAHH activity) [Kaminska and Fox, 1980], The enzyme exhibits a genetic polymorphism with two common alleles which have similar gene frequencies in Germany and Japan (SAHH*1 ~0.96) [Bissbort et al, 1983;Akiyama et al, 1984],…”
Section: Introductionmentioning
confidence: 99%